Evaluasi Program Sentra Latihan Olahragawan Muda Potensial Nasional Universitas Negeri Surabaya - Masaji Dirgantara; Hijrin Fithroni; Heri Wahyudi; Abdul Aziz Hakim (Jurnal Kajian dan Penelitian Umum, 2024)
The Ministry of Youth and Sports established a program for fostering young athletes which was named the Design of the National Sports Advisory Board (DBON), which currently has four centers spread across four universities on the island of Java. The centers in the DBON program are given the Sentra Latihan Olahragawan Muda Potensial Nasional. In this program the coaching carried out is long-term coaching which is targeted for the 2032 Olympics, Brisbane, Australia. This research only focuses on the Surabaya State University's National Potential Young Athlete Training Center, which currently has 3 (three) sports branches and has a total of 24 athletes from all over Indonesia. In the development of the SLOMPN program, it is necessary to periodically evaluate progress. This research method uses a descriptive qualitative research method with the chosen research design being the CIPP model developed by Stufflebeam. Evaluation uses the CIPP model, consisting of elements: context, input, process, and product. This method has been validated by sports science experts. The sample is part of the population taken by the researcher for research. The samples taken in this study consisted of 3 (three) coaches from swimming, archery, and taekwondo, 1 (one) school representative who was the homeroom teacher, and 6 (six) athletes from swimming, archery, and taekwondo. Taekwondo. The results of the research show that the process of fostering achievement and academic achievement at SLOMPN Surabaya State University in terms of context, input, process, and product only requires a little team evaluation and improvement as well as additions to existing facilities and infrastructure. The results of the study also found obstacles regarding athlete, coach and support staff decisions which made there was no definite clarity for athletes, coaches and support staff. The conclusion of this study shows that the entire process of running the Surabaya State University SLOMPN program has been going well, but there still needs to be improvements starting from team coordination, repair and addition of infrastructure and the need for decrees aimed at athletes, coaches and support staff.